PENERAPAN DISIPLIN POSITIF MELALUI SEIGITIGA RESTITUSI UNTUK MENINGKATKAN SIKAP TANGGUNG JAWAB - Aulia Dewi, Agnia; Latifah, Hanny; Akmal, Rudi (Cahaya Smart Nusantara, 2023)
This research was motivated by the low level of students' responsible attitudes in elementary schools, which can be seen from the results of initial observations at SDN 3 Cipareuan and The use of the disciplinary approach that has been used is more focused on punishment, which is less effective in establishing long-term responsibility. So another method is needed, namely by implementing a positive discipline model through the restitution triangle developed by Diane Gossen. This research using a quantitative experimental method with a one group pretestposttest design, the research subjects consisted of 22 class IV students at SDN 3 Cipareuan. Technique Data collection includes observation, questionnaires and documentation. Data analysis carried out using the Wilcoxon test, as well as the N-Gain test to determine the level increasing students' responsible attitudes after implementing positive discipline. Results research shows that the application of positive discipline through the restitution triangle provide a significant influence on increasing the attitude of responsibility the student answered. From the results of observations, students obtained an average score of 70% in the high category. The Wilcoxon test shows a value of 0.00 < 0.05, so the alternative hypothesis is accepted, which means there is a significant increase in student responsibility attitude. The N-Gain test results show an increase of 0.90 which is categorized as a high increase.